MALAY LANGUAGE USE AMONG UKM STUDENTS IN TERMS OF DAILY INTERACTIONS AND AFFAIRS - AMIRUL MUKMININ MOHAMAD (MANU Journal of Humanities, 2022)
This study aims to look at the frequency of Malay language practice by Malay students in higher learning institutions in the aspect of interaction with people around them such as family and acquaintances as well as in public affairs. The survey involved 258 Malay students at The National University of Malaysia (UKM) who attended various undergraduate programs. The data were analysed using a percentage descriptive statistical analysis to find out the frequency value for each Malay language usage situation. The five-point Likert scale of that frequency value is marked with Each Time, Frequent, Sometimes, Rare, and Never. Data collection is done using an online questionnaire through the Google Form application. The percentage analysis recorded a value below 70% for the ‘Every Time’ frequency scale in the use of Bahasa Melayu when with friends (64.4%), when meeting new or unknown people (55.2%), during shopping at shopping malls (58.7%) and when chatting with college friends (66.5%). The results also showed that the use of language in the communication and daily affairs of Malay students at UKM is also dominated by English in certain matters, other than Bahasa Melayu. The findings of this study are expected to contribute to the planning of programs, courses and appropriate measures to inculcate the use of Bahasa Melayu among students in Malaysia.